ANALISIS HUBUNGAN SUHU PERMUKAAN LAUT, KLOROFIL-a DATA SATELIT MODIS DAN SUB-SURFACE TEMPERATURE DATA ARGO FLOAT TERHADAP HASIL TANGKAPAN TUNA DI SAMUDERA HINDIA - Latumeten, Geertruidha Adelheid; Purwanti, Frida; Hartoko, Agus (Management of Aquatic Resources Journal (MAQUARES), 2013)
Tuna is a large pelagic fish that has three characters. First, most of Tuna were found in upwelling and sea water front area. Second, Tuna have a migratory instinct to locate abundant source of food area. Third, each species of Tuna has sub-surface temperature preference The research used explorative method and the sampling method used purposive sampling. Data used in the research are sea surface temperature, chlorophyll-a from the MODIS satellite data and sub-surface temperature from the ARGO Float data. The result has shown that the highest Tuna catch occurs on the east season except for southern bluefin Tuna which was only caught on the west season. The upwelling phenomenon was detected on the west season and the sea water front phenomenon was detected on the east season. Â Analysis of single and multiple correlation between sub surface temperature and Tuna catch has shown high correlation with the coefficient correlation value is above 0.5 for both seasons. Based on the research, yellowfin Tuna has temperature range of 21 â€“ 27 â°C in the depth of 80 m â€“ 100 m, bigeye Tuna is 10 â€“ 23 â°C in the depth of 150 m, albacore is 11 â€“ 19 â°C in the depth of 150 m and southern bluefin Tuna is 12 â€“ 16 â°C in the depth of 200 m.